Future Anxiety Among Young People Affected by War and Armed Conflict: Indicators for Social Work Practice - Nouf M. Alotaibi (Frontiers Media S.A., 2021)
Strengthening the evidence base for professional social work intervention that contributes to providing psychosocial support to international students affected by war and conflict is a major priority as this vulnerable group of youth increases. Therefore, this study aimed to determine the level of future anxiety among international students coming from areas experiencing war and conflict. This study used the descriptive correlative approach, where the future anxiety scale was applied to a sample of 287 international students affected by war and conflicts. Findings showed that there are statistically significant differences between males and females (in favor of females) in the level of the social dimension of future anxiety. The current study results showed a statistically significant relationship between future anxiety and some variables related to war and conflict (living in a war environment - direct and indirect exposure to damage). There are statistically significant differences between those who lived in Yemen at the time of wars and those who did not live (in favor of those who lived in Yemen at the time of wars) in the level of future anxiety. There are also statistically significant differences between those exposed to harm or their family because of the war and those who were not exposed (in favor of those who were exposed) in the level of future anxiety as a whole. The study recommends developing psychosocial support services for this vulnerable group, considering the cultural context to promote women and protect them from discrimination in the services they deserve on an equal basis with men.